PREVALENSI JAMUR PADA PEMERIKSAAN MIKROSKOPIS SPUTUM PASIEN TB DI INSTALASI MIKROBIOLOGI RSUP SANGLAH, DENPASAR, BALI PERIODE 2011 – 2013 - Nugraha, Putu Agoes Adi Ariestyawan; Dwija, Ida Bagus Nyoman Putra (E-Jurnal Medika Udayana, 2017)
(TB) was the second main cause of death by infection all over the world. WHO stated there are 8.6 million new cases of TB in 2012 and 1.3 million cases of death caused by TB. Using Ziehl Neelsen (ZN) methods besides TB bacteria, there were also other organisms identified such as fungal, mostly Aspergillus and Candida. Bali was the province with high cases of TB. But until now there were no data for the prevalence of fungal from TB patient sputum. The research method was a cross sectional using secondary data patient examination report in RSUP Sanglah, Denpasar, Bali since 2011 to 2013. Result will be presented by descriptive analysis. 1318 (13%) fungal sample was positive from total 10.068 sample on January 2011- June 2013. Based on gender, male 840 (63.7%) and female 478 (36.3 %), meanwhile by age group <5 years old 4 (0.3%); child (6-12 years) 9 (0.7%); teen (13-20 years) 18 (1.4%); adult (21-55 years) 655 (49.7%); and elderly ( >50 years) 632 (48%) Prevalence of positive fungal sample was 13%, based on gender, male show higher number (63.7%), and highest number of sample in age group 21 to 50 years old (49.7%). This could be affected by various factors such as research design, number of sample, time, and place of the research. Keywords: tuberculosis (TB), Ziehl Neelsen (ZN), fungal